Do Foreign Capital and Financial Development Affect Clean Energy Consumption and Carbon Emissions? Evidence from BRICS and Next-11 Countries - Shahbaz, Muhammad; Destek, Mehmet Akif; Polemis , Michael L. (SPOUDAI Journal of Economics and Business, 2018)
This study investigates the main interrelations generated by the impact of foreign capital along with financial development on clean energy consumption and environmental degradation proxied by the inclusion of CO2 emissions. In doing so, we used panel data techniques targeted at BRICS and Next-11 countries spanning the period 1992-2016. Our paper strongly accounts for the existence of crosssectional dependence and non-stationarity usually ignored by the other empirical studies. In case of BRICS, the empirical findings reveal that economic growth increases clean energy consumption while financial development reduces it. On the contrary, foreign capital inflows do not appear to have a statistically significant effect on clean energy. We argue that, economic growth, foreign capital inflows and financial development increase CO2 emissions, while clean energy consumption reduces environmental degradation by mitigating carbon emissions in BRICS countries. In case of Next-11 countries, empirical findings indicate that economic growth and foreign capital have positive effect on clean energy consumption. However, economic growth and financial development increases CO2 emissions in N-11 countries. JEL Classifications: G1, Q4, Q5